2015
DOI: 10.1016/j.chemosphere.2014.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic hazard assessment of a commercial sample of naphthenic acids

Abstract: This paper presents chemical composition and aquatic toxicity characteristics of a commercial sample of naphthenic acids (NAs). Naphthenic acids are derived from the refining of petroleum middle distillates and can contribute to refinery effluent toxicity. NAs are also present in oil sands process-affected water (OSPW), but differences in the NAs compositions from these sources precludes using a common aquatic toxicity dataset to represent the aquatic hazards of NAs from both origins. Our chemical characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…NA) and non-polar (e.g. hydrocarbons) (Conly et al, 2002;Headley and McMartin, 2004;Swigert et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NA) and non-polar (e.g. hydrocarbons) (Conly et al, 2002;Headley and McMartin, 2004;Swigert et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…GCxGC-MS) has also led to partial resolution (usually following derivatisation) even of UCMs of more polar petroleum constituents, such as petroleum acids (e.g. naphthenic acids (NAs), Bowman et al, 2014;Swigert et al, 2015). Such components become more quantitatively important following biodegradation of petroleum, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical characterization of commercial NAs revealed that the majority of NAs in commercial mixtures were composed of 1 to 3 rings [29]. These commercial preparations also contain monoaromatic acids and non-acids (both found in the light PAHs fraction), PAHs and sulfur heterocyclic hydrocarbons.…”
Section: Discussionmentioning
confidence: 99%
“…Storage of OSPW in close proximity to natural water sources (rivers, ponds, marshes) is of concern due to the possibility of tailings pond leakage and possible seepage into groundwater. Analysis of groundwaters and adjacent natural waters is required in order to monitor for possible leakage, seepage or accidental discharge, as it has been reported that OSPW is toxic to aquatic organisms (Allen, 2008;Marentette et al, 2015;Swigert et al, 2015). The caustic hot water extraction process used to extract the bitumen from the oil sands is known to concentrate the acidic species, namely naphthenic acids (NAs), and related components which are collectively known as naphthenic acid fraction compounds (NAFCs) (Allen, 2008;Headley and McMartin, 2004;Shell Canada Ltd., 2016).…”
Section: Introductionmentioning
confidence: 99%